Analysis of an articulated figure skating boot - Richards, J. G.; Bruening, D. A. (2006)
The purpose of this project was to examine the effectiveness of an articulated figure skating boot prototype in enabling a skater to attenuate the impact force at landing. Kinetic and kinematic variables were compared to test the hypothesis that articulated boots can effectively help reduce jump landing forces compared to standard boots.